Influence of speed-related auditory feedback on braking in a 3D-driving simulator. (January 2017) - Bringoux, Lionel; Monnoyer, Jocelyn; Besson, Patricia; Bourdin, Christophe; Denjean, Sébastien; Dousset, Erick; Goulon, Cédric; Kronland-Martinet, Richard; Mallet, Pierre; Marqueste, Tanguy; Martha, Cécile; Roussarie, Vincent; et al.
Highlights: The role of continuous speed-related auditory feedback on braking was investigated. Acoustic cues from an electric car did not impact braking initiation/regulation. Synthesized auditory feedback based on the Shepard-Risset glissando was manipulated. Speed-related synthesized sound variations allowed for subtle braking regulation. These adjustments depended on dynamics of auditory feedback and time for braking. Abstract: Although discrete auditory stimuli have been found useful for emergency braking, the role of continuous speed-related auditory feedback has not been investigated yet. This point may though be of importance in electric vehicles in which acoustic cues are drastically changed. The present study addressed this question through two experiments. In experiment 1, 12 usual drivers were exposed to naturalistic auditory feedback mimicking those issued from electric cars, while facing dynamic visual scenes in a 3D driving simulator. After being passively travelled up to a sustained constant speed, subjects had to stop their car in front of a traffic light that unexpectedly turned to red. Modifications of the speed-related auditory feedback did not impact braking initiation and regulation. In experiment 2, synthesized auditory feedback based on the Shepard-Risset glissando was provided to a new sample of 15 usual drivers in the same task. Pitch variations of this acoustic stimulus, although not scaled to an absolute speed, were manipulated as a function of visual speed changes. Changing the mapping between pitch variations of the synthesized auditory feedback and visual speed changes induced adjustments on braking which depended on acceleration/deceleration feedback. These findings stressed the importance of the acoustic content and its dynamics for car speed control.